Targeting MERTK tyrosine kinase: Virtual screening and molecular dynamics insights for anti-cancer drug development - Kashif Kifayat; Kamaljot Singh; Mahmood Khan; Dur E. Maknoon Razia; Sara Khan; Chengyong Dong; Liming Wang (PLoS ONE, 2025)
Global public health facing serious challenges due to the incidence of cancer and the growth of treatment resistance. Mer-tyrosine kinase plays a crucial role in cell biology and correlated with many cancers such as Epithelial ovarian cancer, liver cancer, breast cancer, Metastatic melanoma, and Acute myeloid leukemia (AML). Hence the identification of novel drug for MERTK protein is extreme important. In this research, we used computational techniques, molecular operating environment (MOE 2015) for virtual screening with drug like natural compounds library. We used known compound UNC2025 as positive control and one million compounds was retrieved from different databases (OTAVA, ZINC, ChEMBL) and docked with MERTK protein. Out of million compounds the 4 top hit inhibitors chosen from docking were further screened for ADMET profiling confirming their compliance with drug designing and toxicological principle and subjected to molecular dynamic (MD) simulation and MM-PBSA analysis. The results of these analyses showed that only four compounds that make strong interactions with MERTK protein via highest binding affinity hydrogen bond and hydrophobic contacts (lig1, lig2, lig3, lig4). The computed binding affinity ranges from –22.977 to –18.707 kcal/mol. The increased helix and reduced β–sheet contents in MERTK on the binding of top hit candidates depicted the higher structural stability of MERTK, rather than MERTK alone and MERTK–UNC2025. The study finds critical residues which serve a vital part in binding with the inhibitor and the active site of the MERTK protein, i.e. , Phe598, Gly599, Lys619, Arg629, Glu633, Glu637, Arg722, Asp723, Arg727, Asp741, Gly743, Leu744, Lys746, Arg758, Ala760, and Lys761 through decomposed binding free energy analysis. This study focuses on the pursuit of several MERTK protein targets, which could have consequences for the development of novel therapeutics for various cancers.